A relação entre o valor da marca e a Intenção de compra pela perspectiva do consumidor de smartphones - Vieira, Vitor Azzari (2018)
Currently one of the objects most used by the population are smartphones, which allow people to have in their hands tools never before imagined. Its growth is due to the great and current technological advance. Linked to the environment of high competitiv